Analysis of Corrosion Rate Al 7075 Using Seawater and Rainwater Media Using the K2CRO4 - Paramarta, Brillian Rakha; Sehono, Sehono; Putra, Ikbal Rizki (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2024)
Aluminum is one of the most widely used materials today due to several advantages, including its lightweight nature, relatively high tensile strength, good formability, corrosion resistance, and non-magnetic properties, making it a preferred choice in industries such as aerospace. However, metals, including 7075 aluminum alloy commonly used in the aerospace industry, are still susceptible to corrosion in corrosive environments. One effective method to control corrosion is the use of inhibitors. An inhibitor is a chemical substance that, when added in small amounts to a corrosive environment, can effectively slow down or reduce the corrosion rate. This study investigates the corrosion rate using the potentiodynamic polarization method (Tafel plot) in seawater from Parangtritis Beach and rainwater from Yogyakarta City. The inorganic inhibitor used in this research is K₂CrO₄ with a concentration of 0.3%. The results show that the corrosion rate in seawater without inhibitors (pH 7.34) is 0.027799 mm/yr, while with inhibitors (pH 7.50), it decreases to 0.0053243 mm/yr. Similarly, the corrosion rate in rainwater without inhibitors (pH 6.66) is 0.0021987 mm/yr, while with inhibitors (pH 7.74), it reduces to 0.0017807 mm/yr. These findings demonstrate the effectiveness of K₂CrO₄ inhibitors in minimizing corrosion rates in both seawater and rainwater environments.